PHILOSOPHICAL APPROACHES TO THE RESEARCH OF LIBERALISM IN THE FIELD OF CRIME AND PUNISHMENT IN NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
The article examines the socio-anthropological principles and characteristics, theoretical and methodological foundations, necessity, and relevance of liberalization in the field of crime and punishment, and analyzes its socio-philosophical, moral, spiritual, and legal classification and specific features in this process.